Cistercian Europe. Architecture of contemplation. By Terryl N. Kinder. Pp. 407 incl. numerous black-and-white and colour plates. Grand Rapids, Mich.: Eerdmans/Kalamazoo, Mich.: Cistercian Publications, 2002. £49.95 (70). 0 8028 3887 1; 0 87907 391 8 - Lovatt, Roger (The journal of ecclesiastical history, 2004)
Cistercian Europe. Architecture of contemplation. By Terryl N. Kinder. Pp. 407 incl. numerous black-and-white and colour plates. Grand Rapids, Mich.: Eerdmans/Kalamazoo, Mich.: Cistercian Publications, 2002. £49.95 ($70). 0 8028 3887 1; 0 87907 391 8 - Volume 55 Issue 3